Rancangan Standard Instrument Departure Runway 18 di Perum LPPNPI Cabang Manado - Charisma Topan HDP; Rany Adiliawijaya; Rino Laharto (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
This study aims to examine SID RNP 1 to support flight efficiency using SID Luang One Departure. This research was conducted at Approach Control Unit at AirNav Indonesia Manado Branch. Research methods are Research and Development Level 1. Results of this study conclude, the aircraft is inefficient using SID Luang One Departure. According to results of interviews with ATCs in the Manado Approach, data on 90% compliance with RNP 1, need for draft revision of the SID Space One Departure for flights to ATS Route W32. Design of appropriate procedures to support efficiency is the 5% gradient Free from Obstacles